Analysis of Impact of CAR, NPF, BOPO on Profitability of Islamic Banks (Year 2015-2017) (Journal of Islamic Economic Laws, 2019)
Islamic banks have been known as the resistant banks to the global crisis that hit Indonesia a few years ago. The unique maintenance of Islamic bank performance leads to business continuity. Some Islamic bank performance can be measured by its profitability. There are some factors that affect the profitability Islamic bank and used in this study including CAR, BOPO, and NPF. While the purpose of this study is to determine the effect of CAR, BOPO and NPF on the profitability of Islamic commercial banks. The population of this research is the Islamic commercial bank whose financial statements have been published to the statistics of Islamic banks from 2015 -2017. This research used secondary data from OJK website. Data analysis in this paper conducted multiple linear regression analysis method. The results of this study indicate that the BOPO variable has a significant effect on ROA. On the other hand  CAR and NPF variables have no significant effect on ROA.